2022
DOI: 10.3390/cancers14163931
|View full text |Cite
|
Sign up to set email alerts
|

An International Comparison of Presentation, Outcomes and CORONET Predictive Score Performance in Patients with Cancer Presenting with COVID-19 across Different Pandemic Waves

Abstract: Patients with cancer have been shown to have increased risk of COVID-19 severity. We previously built and validated the COVID-19 Risk in Oncology Evaluation Tool (CORONET) to predict the likely severity of COVID-19 in patients with active cancer who present to hospital. We assessed the differences in presentation and outcomes of patients with cancer and COVID-19, depending on the wave of the pandemic. We examined differences in features at presentation and outcomes in patients worldwide, depending on the waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The actual number of patients with cancer and COVID-19 may have not been accurate with some patients having asymptomatic or minimally symptomatic COVID-19 not being tested and consequently not being included in the studies ( 31 , 32 , 33 ). Another study shown a decrease in mortality across the wave during the acute phase of COVID-19 infection with a possible benefit of the steroid ( 34 ). Possible explanations were the difference of duration of follow up or the fewer number of different countries with less heterogeneity in the management of COVID infection and therefore a better management of patients and their complications.…”
Section: Discussionmentioning
confidence: 99%
“…The actual number of patients with cancer and COVID-19 may have not been accurate with some patients having asymptomatic or minimally symptomatic COVID-19 not being tested and consequently not being included in the studies ( 31 , 32 , 33 ). Another study shown a decrease in mortality across the wave during the acute phase of COVID-19 infection with a possible benefit of the steroid ( 34 ). Possible explanations were the difference of duration of follow up or the fewer number of different countries with less heterogeneity in the management of COVID infection and therefore a better management of patients and their complications.…”
Section: Discussionmentioning
confidence: 99%